RECONSTRUCTION OF LEGAL PROTECTION FOR SCHOOL-DROPOUT CHILDREN REGARDING THEIR RIGHT TO RECEIVE EDUCATION - Syahputra, Amry (International Journal of Law Social Sciences and Management, 2024)
This research aims to reconstruct the legal protection framework for children who are disconnected from the education system and examine efforts that can be made to ensure their right to education is well-protected. The research results indicate that despite the existence of legal instruments guaranteeing children's right to education, implementation still faces various challenges, especially in the case of school dropout children. Factors such as unequal access, poverty, and psychosocial challenges can be significant barriers for these children to obtain proper education. Therefore, this research recommends the expansion and improvement of existing regulations, increased accessibility to education for school dropout children, and strengthening legal protection mechanisms to ensure that children's right to education can be effectively realized. Thus, the reconstruction of legal protection is expected to contribute positively to fulfilling the right to education for children marginalized from the formal education system.